Measuring the developmental function of peer review: a multi-dimensional, cross-disciplinary analysis of peer review reports from 740 academic journals - Daniel Garcia-Costa; Flaminio Squazzoni; Bahar Mehmani; Francisco Grimaldo (PeerJ, 2022)
Reviewers do not only help editors to screen manuscripts for publication in academic journals; they also serve to increase the rigor and value of manuscripts by constructive feedback. However, measuring this developmental function of peer review is difficult as it requires fine-grained data on reports and journals without any optimal benchmark. To fill this gap, we adapted a recently proposed quality assessment tool and tested it on a sample of 1.3 million reports submitted to 740 Elsevier journals in 2018–2020. Results showed that the developmental standards of peer review are shared across areas of research, yet with remarkable differences. Reports submitted to social science and economics journals show the highest developmental standards. Reports from junior reviewers, women and reviewers from Western Europe are generally more developmental than those from senior, men and reviewers working in academic institutions outside Western regions. Our findings suggest that increasing the standards of peer review at journals requires effort to assess interventions and measure practices with context-specific and multi-dimensional frameworks.